Book Review: Jake H. Davis (Ed.), A Mirror Is for Reflection: Understanding Buddhist Ethics. (January 2019) - Tewari, Anil Kumar
Jake H. Davis (Ed.), A Mirror Is for Reflection: Understanding Buddhist Ethics, New York, NY: Oxford University Press, 2017. 358 pages. ₹1, 395, US69.95. ISBN 978-0-19-049977-8 (hardcover), ISBN 978-0-19-049976-1 (paperback).